Сметководствени и финансиски аспекти на пазарот на капитал во Република Македонија - Јованоска, Дијана (Економски факултет, УКИМ, Скопје, 2013)
The subject of study in this work are accounting and financial aspects of the capital market in Republic of Macedonia. Since the capital market is the basic development factor of each economy, I think that the existence of trust in the capital market is one of the fundamental conditions for inflow and acumulation of capital in the country via attracting investments. Therefore, research of accounting and financial aspects of the capital market in Macedonia is of special importance. Once analisys of accounting and financial aspects of the capital market in Macedonia is completely done, it is necessary to check their compliance with EU regulations. The need of additional activities which should be taken by the Republic Macedonia for complete compatibility with EU regulations should be analyzed too.
Accounting and financial aspects of the capital market in Republic of Macedonia
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубиша Јаневски.
Keywords: capital market, accounting aspects, financial aspects, securities, trading companies, investment funds, corporate companies, risk, Europian Union, Intrenational Accounting Standards, International Financial Reporting Standards.